Growth and welfare effects of health care in knowledge based economies - Michael Kuhn; Klaus Prettner (Vienna University of Technology, Institute of Mathematical Methods in Economics, Research Group Economics, 2012)
We study the effects of a labor-intensive health care sector within an R&D-driven growth model with overlapping generations. Health care increases longevity and labor participation/productivity. We examine under which conditions expanding health care enhances growth and welfare. Even if the provision of health care diverts labor from productive activities, it may still fuel R&D and economic growth if the additional wealth that comes with expanding longevity translates into a more capital/machine- intensive final goods production and, thereby, raises the return to developing new machines. We establish mild conditions under which an expansion of health care beyond the growth-maximizing level is Pareto-improving.
Keywords: I15; I18; O11; O41; O43; 330; endogenous growth; mortality; (Blanchard) overlapping generations; health care; research and development; sectoral composition